(untitled) (Fiep Bulletin - online, 2013)
The main objective of this study was to verify the children’s ability in corporal mastery in movement shifts to the right and the left and rhythmic structure. Specifically, it aimed to verify the children’s skills on lateral control when starting the test, as facts ascertainment, which is the search for answers to our concerns regarding the motor skills of adolescents from three schools of the urban area of Jardim-MS. The adolescents were allowed by their parents and other guardians to integrate the study. The hypothesis under verification is related to three facts: if gender, weight and stature interfere in rhythm, time, identification of right and left, and start the test correctly. It was found that the gender did not interfere on accomplishing the test of rhythm, unlike weight, which interfered in the performance average time of the test of agility, and the height interfered in the rhythm. The other cases analyzed, no significant differences were found.